Legal Steps to Resolve Labor Relations Problems (Drivers) in Logistics and Land Transportation Companies - Maniur sinaga (Jurnal Indonesia Sosial Teknologi, 2024)
This study investigates legal steps in resolving labor relations problems, primarily related to drivers, in logistics and land transportation companies. By analyzing employment contracts, consultation with legal experts, amicable negotiations, mediation or arbitration, and the possibility of filing a lawsuit in court, this study aims to understand the dispute resolution process comprehensively. The research method used is a case study by analyzing several cases of logistics and land transportation companies. The results showed that the implementation of these legal measures can provide fair solutions and minimize conflicts between related parties, as well as ensure the enforcement of rights in accordance with applicable legal provisions. The implication of this research is the importance of understanding and using legal measures to solve labor problems effectively and efficiently in the context of the logistics and land transportation industry.